Analisis Kesediaan Membayar Air Bersih dan Sanitasi Rumah Tangga di Indonesia - Watekhi, Watekhi; Hartono, Djoni; Dewi, Rika Kumala (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
Using Logistic Regression and Hedonic Price Model, this study aims to find the social-economic factors influencing the demand and willingness to pay (WTP) for clean water supply and proper sanitation. This study find that education and age of household head are the affecting factors. Also, it found that per capita expenditure affects the availability of access for sanitation and clean water for all household group. WTP for clean water and sanitation in urban is greater than in rural. In additions, WTP of non poor households are greater than poor household, except for urban area.